Alternative Pathways of Change in Professional Services Firms: The Case of Management Consulting. (7th January 2013) - Kipping, Matthias; Kirkpatrick, Ian
Abstract : This paper contributes to the debate about new organizational forms in professional service firms (PSFs) by suggesting an alternative to extant accounts of how change takes place. To explain the displacement of community forms of organizing by more corporate forms, much of the literature has so far focused on intra‐archetype adaptation and evolutionary processes, looking mainly at established PSFs in law and accounting. Drawing on ideas from the sociology of professions and institutional theory, we suggest that, in more weakly regulated and open professional fields, change might also come from firms entering from the margins or the outside and bringing with them different models of organizing. We explore this possibility through a historical case study of the management consulting field in the UK over a 50 year period, based on a wide range of data sources. Our study shows that despite good intentions at the outset the main professional association was unable and – increasingly – unwilling to restrict entry. This resulted in growing fragmentation of the field through new entrants and, consequently, in greater diversity of organizational forms. Such findings draw attention not only to alternative pathways of change in PSFs, but also to the importance of distinguishing between professional organizational fields more generally.